Beyond data labor: sowing synthesis science in the Global South - André L. Luza; André L. Giles; Pedro J. Bergamo; Grasiela Casas; Alice R. de Moraes; Marina M. Monteiro; Herval V. Pinto-Junior; Kátia F. Rito; Ana C. Rorato; Lis F. Stegmann; Gisele R. Winck; Marisa Mamede (Perspectives in Ecology and Conservation, 2023)
Synthesis science is an emergent research field for harmonizing different data, concepts, and theories to create new insights and endorse novel approaches. Here we provide a brief general overview of synthesis science, emphasize the geographically biased location of synthesis centers一particularly their paucity in the Global South一and highlight the pioneering role of the Synthesis Center on Biodiversity and Ecosystem Services (SinBiose, CNPq) concerning transdisciplinary aspirations in the Global South. Working with the ecosystem service dimension requires breaking discipline boundaries to approach society, stakeholders, and decision-makers, which SinBiose fosters and is rarely found elsewhere. This article features a “Brazilian experience” of synthesis science through the perception of SinBiose’s postdoctoral researchers, which have a central role in the workflow as the only professionals dedicated exclusively to the projects. As a conclusion, we present recommendations for improving the support for postdoctoral researchers and arguments for a continued funding of synthesis science in Brazil.